THE EFFECT OF E-LEARNING BASED LEARNING DURING THE COVID-19 PANDEMIC ON ACCOUNTING COMPUTER LEARNING RESULTS IN CLASS XII STUDENTS IN ACCOUNTING EXPERTISE PROGRAM IN SMK NEGERI I PANGKEP - Regina Regina; Sahade Sahade; M. Yusuf A. Ngampo; Abd. Rijal (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the magnitude of the influence of E-learning-based learning during the Covid-19 pandemic on student accounting learning outcomes at SMK Negeri 1 Pangkep. The variables in this study are E-learning-based learning during the Covid-19 pandemic as the independent variable and learning outcomes as the dependent variable. The population in this study were all students of the accounting expertise program at SMK Negeri 1 Pangkep consisting of 144 students. The sampling technique used a proportionate stratified random sampling technique with a total sample of 59 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive analysis of percentages, instrument testing and hypothesis testing. Instrument test consists of validity test and reliability test. The hypothesis test consists of simple linear regression analysis, t-test, and coefficient of determination. The results of this study indicate that students have difficulty learning Myob Accounting online during the Covid-19 pandemic with a fairly high level of difficulty obtained from the indicators, namely technical difficulties with a percentage of 43% which are categorized as quite high, which includes internet signal strength in the high category, limited internet quota with low category and supporting devices with low category. Then the indicator of student adaptation difficulties with a percentage of 57% is categorized as quite high which includes unconducive home conditions in the low category, not used to online learning in the high category, more online assignments in the high category and difficulty dividing time in the sufficient category. The indicator of lecturer unpreparedness with a percentage of 67% is categorized as high which includes explanations that are still lacking in the high category, the limited form of material provided is in the high category and the limited applications used in online learning are in the high category. Furthermore, based on the results of the regression analysis, the simple linear regression equation model Y' = 31.092 + 0.375X means that E-learning-based learning has a positive effect on learning outcomes where each additional value of one independent variable increases the value of the dependent variable by 0.375 units. From the results of the analysis of the coefficient of determination (r = 12.7%, which means that E-learning-based learning contributes to student learning outcomes by 12.7% and the remaining 87.3% is influenced by other factors. Meanwhile, the t-test analysis results obtained a significant value 0.003 <0.05 which means that the independent variable has a significant effect on the dependent variable, thus the hypothesis is accepted.